Biomarkers of Human Cardiopulmonary Response After Short-Term Exposures to Medical Laser-Generated Particulate Matter From Simulated Procedures: A Pilot Study. Issue 9 (September 2016) - Lopez, Ramon; Farber, Mark O.; Wong, Vincent; Lacey, Steven E.
Abstract : Objective: We conducted an exposure chamber study in humans using a simulated clinical procedure lasing porcine tissue to demonstrate evidence of effects of exposure to laser-generated particulate matter (LGPM). Methods: We measured pre- and post-exposure changes in exhaled nitric oxide (eNO), spirometry, heart rate variability (HRV), and blood markers of inflammation in five volunteers. Results: Change in pre- and post-exposure measurements of eNO and spirometry was unremarkable. Neutrophil and lymphocyte counts increased and fibrinogen levels decreased in four of the five subjects. Measures of HRV showed decreases in the standard deviation of normal between beat intervals and sequential 5-minute intervals. Conclusion: These data represent the first evidence of human physiologic response to LGPM exposure. Further exploration of coagulation effects and HRV is warranted.